PENGARUH VARIASI PENAMBAHAN SUSU SKIM TERHADAP KADAR ASAM AMINO PADA YOGURT SARI KACANG MERAH (Phaseolus vulgaris L.) - Dita Ayu Purwani (Jurnal Riset Sains dan Kimia Terapan, 2021)
Yoghurt is a probiotic drink containing amino acids. The basic ingredients of yoghurt is cow's milk. But cow's milk is easy to spoil and therefore it replaced with red beans. This study aims to determine the effect of addition skim milk to red bean extract to produce yoghurt with six variations. The amino acids levels in red bean extract yoghurt are analyzed using HPLC. The optimum concentration in 6 concentration variations is 80% skim milk and 20% red bean extract. Based on the results of the HPLC chromatogram showed that the amino acid glutamatic has the highest peak with levels of 1,74 x w/w